(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Nursing expertise plays a crucial role in strengthening epidemiology and surveillance within public health systems. This paper explores the multifaceted contributions of nurses to data collection, analysis, and management of surveillance systems, highlighting their role in promoting population health and preventing disease spread. Drawing upon principles of epidemiology and public health surveillance, as well as core competencies for public health nursing, this paper elucidates the various ways in which nurses engage in surveillance activities, including patient assessments, health records documentation, surveillance systems reporting, data analysis, quality improvement initiatives, and community health assessments. Through interdisciplinary collaboration, communication, and advocacy, nurses enhance the effectiveness and reliability of public health surveillance efforts, ultimately improving health outcomes and reducing the burden of disease within communities.